Retarded saturation of the areal capacitance using 3D-aligned MnO2 thin film nanostructures as a supercapacitor electrode - Green Kim (Nature Portfolio, 2017)
Abstract The supercapacitive properties of manganese oxide (MnO2) thin films electrodeposited on three-dimensionally (3D) aligned inverse-opal nickel nanostructures are investigated. Compared to conventional planar or two-dimensionally (2D) aligned nanostructures, 3D-aligned nanostructures can provide considerably increased and controllable contacts between the electrode and electrolyte. As a result, saturation of the areal capacitance with the electrode thickness and associated decrease of the specific capacitance, C sp , become much slower than those of the planar and 2D-aligned electrode systems. While, for planar MnO2 electrodes, the C sp of a 60-cycle electrodeposited electrode is only the half of the 10-cycle electrodeposited one, the value of the 3D-nanostructured electrode remains unchanged under the same condition. The maximum C sp value of 864 F g−1, and C sp retention of 87.7% after 5000 cycles of galvanostatic charge-discharge are obtained. The voltammetric response is also improved significantly and the C sp measured at 200 mV s−1 retains 71.7% of the value measured at 10 mV s−1. More quantitative analysis on the effect of this 3D-aligned nanostructuring is also performed using a deconvolution of the capacitive elements in the total capacitance of the electrodes.